E2/ER β inhibit ISO-induced cardiac cellular hypertrophy by suppressing Ca2+-calcineurin signaling. - Cheng-Yen Tsai; Wei-Wen Kuo; Marthandam Asokan Shibu; Yueh-Min Lin; Chien-Nam Liu; Yi-Hui Chen; Cecilia-Hsuan Day; Chia-Yao Shen; Vijaya Padma Viswanadha; Chih-Yang Huang (PLoS ONE)
Cardiovascular incidences are markedly higher in men than in pre-menstrual women. However, this advantage in women declines with aging and therefore can be correlated with the sex hormone 17β-Estradiol (E2) which is reported to protect heart cells by acting though estrogen receptors (ERs). In this study we have determined the effect of E2/ERβ against ISO induced cellular hypertrophy in H9c2 cardiomyoblast cells. The results confirm that ISO induced cardiac-hypertrophy by elevating the levels of hypertrophy associated proteins, ANP and BNP and further by upregulating p-CaMKII, calcineurin, p-GATA4 and NFATc3 which was correlated with a significant enlargement of the H9c2 cardiomyoblast. However, overexpression of ERβ and/or administration of E2 inhibited ISO-induced hypertrophy in H9c2 cells. In addition, E2/ERβ also inhibited ISO-induced NFATc3 translocation, and reduced the protein level of downstream marker, BNP. Furthermore, by testing with the calcineurin inhibitor (CsA), it was confirmed that calcineurin acted as a key mediator for the anti-hypertrophic effect of E2/ERβ. In cells treated with calcium blocker (BATPA), the inhibitory effect of E2/ERβ on ISO-induced Ca2+ influx and hypertrophic effects were totally blocked suggesting that E2/ERβ inhibited calcineurin activity to activate I-1 protein and suppress PP1, then induce PLB protein phosphorylation and activation, resulting in Ca2+ reuptake into sarcoplasmic reticulum through SR Ca2+ cycling modification. In conclusion, E2/ERβ suppresses the Ca2+ influx and calcineurin activity induced by ISO to enhance the PLB protein activity and SR Ca2+ cycling.